Electrolytic treatment of wastewater containing n-phenyl-n '-1,3-dimethylbutyl-p-phenylenediamine - Inazaki, T. H. [UNESP]; Moraes, P. B. [UNESP]; Piao, A. C. S. [UNESP]; Bidoia, Ederio Dino [UNESP] (Selper Ltd, Publications Div, 2008)
This study investigated the effects of electrolytic treatment using Dimensionally Stable Anode (DSA, 70%TiO2/30%RuO2) type electrodes in simulated wastewater containing aromatic amine n-phenyl-n'-1,3-dimethylbutyl-p-phenylenediamine (Flexzone 7P). A low direct current density of 0.025 A cm(-2) was applied for periods up to 60 minutes and a 52.6% decrease in Flexzone 7P concentration was observed. Ultraviolet-visible spectra, gas chromatography, toxicity and biodegradation tests were carried out with the aim of verifying the toxic by-products that were formed. Ultraviolet-visible spectra of simulated wastewater exhibited changes in the aromatic amine's molecular structure. Additionally, based on the S. cerevisiae toxicity test, it was observed that detoxification of the wastewater occurred after 15 minutes of electrolysis. It was also observed that five minutes of treatment were sufficient to improve the biodegradation rate, determined through the respirometric Bartha method.
Keywords: electrolytic treatment; industrial wastewater; DSA electrodes; DPA degradation